Heterotopia and cultural activism – the case of Hamburg’s Gängeviertel - Helten, Michael (DIE ERDE – Journal of the Geographical Society of Berlin, 2015)
This paper investigates the Gängeviertel movement in Hamburg and the place which the activists have (re)constructed since its occupation in 2009 through the lens of Foucault’s (1986) concept of heterotopia. In the light of the recent debate about the role of cultural activism in the contemporary struggle about urban development, it explores the question which spatial practices and structures have evolved as oppositional to or in alignment with the neoliberal status quo of Hamburg’s spatial policy. Based on a qualitative case-study approach, the research was carried out in 2013. By using the analytical categories built environment, social practice and neoliberal normalisation, it illustrates that the Gängeviertel is characterised by practices that position it simultaneously both in- and outside of the neoliberal logic.